2016
DOI: 10.1016/j.jcrs.2015.11.048
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a torsional and a standard tip with a monitored forced infusion phacoemulsification system

Abstract: None of the authors has a financial or proprietary interest in any material or method mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 6 publications
0
7
0
1
Order By: Relevance
“…Figure 1: Effect of time on efficiency using the humidity chamber method. While performing a recent study comparing the efficiency of two tips (Vegunta S, Christensen MD, Boulter T, Jensen JD, Olson RJ; unpublished data), our team observed efficiency times that were drastically different from previous work showing that a comparison of two tips typically yields similar efficiency times when the power setting is the same for both tips [12]. We thought the abnormal efficiency times may have been related to the duration of the experiment.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Figure 1: Effect of time on efficiency using the humidity chamber method. While performing a recent study comparing the efficiency of two tips (Vegunta S, Christensen MD, Boulter T, Jensen JD, Olson RJ; unpublished data), our team observed efficiency times that were drastically different from previous work showing that a comparison of two tips typically yields similar efficiency times when the power setting is the same for both tips [12]. We thought the abnormal efficiency times may have been related to the duration of the experiment.…”
Section: Discussionmentioning
confidence: 64%
“…Another study showed that a 0.9 mm, 30-degree angled tip is most efficient when compared to similar 1.1 mm and 0.7 mm tips [8]. This is just a sampling of the many papers that have clarified clinical arguments about superiority in instrumentation definitively and for the first time [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. Figure 1: Effect of time on efficiency using the humidity chamber method.…”
Section: Discussionmentioning
confidence: 99%
“…Efficiency times were averaged and the SDs were calculated. Previous studies13,517,1922 considered all data points more than two SDs from the mean as outliers and removed them. Utilizing these same two SDs as cutoff was considered necessary for this study because research shows that outside of two SDs, data points likely represent very hard lenses that require more time to emulsify 28.…”
Section: Methodsmentioning
confidence: 99%
“…These settings include the aspiration flow rate, level of vacuum at the tip, and magnitude of ultrasound energy. A previous series of studies have determined the optimal settings for lens removal during the quadrant removal portions of the surgery 126. However, the optimal settings for the grooving step, the initial step of phaco, have not yet been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Durch die veränderte Flüssigkeitskontrolle und die Modifikation der Spitze des Phakoemulsifikationshandgriffs können die Phako-energie und die Turbulenzen in der Vorderkammer verringert werden [14]. Damit ist die Aufarbeitung des Linsenkerns schneller und weniger traumatisch durch Linsenfragmente, die bei der Aufarbeitung durch Turbulenzen eine mechanische Schädigung des Endothels verursachen.…”
Section: Diskussionunclassified